Taking utilitarianism seriously - Woodard, Christopher 1971- (Oxford University Press, 2019)
Utilitarianism is the idea that ethics is ultimately about what makes people's lives go better. While utilitarian ideas remain highly influential in politics and culture, they are subject to many well-developed philosophical criticisms, such as the claim that utilitarianism requires too much of us and the view that it does not respect individuals' rights. The theory is widely thought by philosophers to be the least plausible form of consequentialism, hampered by its excessive simplicity. In Taking Utilitarianism Seriously, Christopher Woodard argues that it is not defeated by the standard objections. He presents a new and rich version of utilitarianism that can answer all six commons objections plausibly and, in doing so, launches a state-of-the-art defence of the utilitarian tradition, which has greater resources than its critics have often assumed. Far from being excessively simple, utilitarianism is able to account for much of the complexity and nuance of everyday ethical thought. And rather than being quickly dismissed, utilitarian approaches to moral and political philosophy are due for renewed development and discussion.